Management and outcomes of pediatric neuroendocrine tumors - A systematic review of published studies - Tasto, Oona; Raitio, Arimatias; Losty, Paul D (Netherlands, 2026)
Neuroendocrine tumors (NETs) are rare in the pediatric age group with studies reportedly showing increased incidence in females. The appendix appears to be the most common tumor site, but NETs can arise almost anywhere in the body. Due to rarity, comprehensive reports detailing outcomes are sparse and often based on limited index case numbers. This study aims to systematically analyze outcome metrics of pediatric NET whilst identifying pertinent risk factors for mortality. Medline/Embase databases were searched according to PRISMA guidelines. Final analysis included 83 studies with 3829 NET patients (1917 females - 52 %). Individual patient data was available in 522 patients (49 studies) with a mean follow-up period of 67 months. The most common tumor sites included appendix (30 %), adrenal gland (19 %), pancreas (19 %), and bronchus/lungs (14 %). Surgical tumor resection was the mainstay of treatment while 23 patients (5 %) were managed medically. Recurrence(s) were observed in 35 patients (8 %). Chemo/radiotherapy was reported in 48 patients (12 %). Most patients (94 %) survived - 86 % (n = 378) with no evidence of disease, 8 % (n = 37) were alive with disease and 29 (6 %) died of progressive disease. Positive margins at primary operation, metastatic disease, and large tumor size were associated with mortality (p = 0.0006, <0.0001, and 0.018, respectively). Significantly higher mortality was observed with NETs originating from the liver and thymus. These findings affirm that despite predominantly favorable outcome, complete surgical resection (R0) is crucial, as positive surgical margins predispose to mortality. Similarly, larger tumor size and certain anatomical tumor sites are associated with worse outcome(s).